Assessment of somatic developmental status of the male students from various fields of study at the Faculty of Physical Education and Sport in Biala Podlaska - Wasiluk, Agnieszka; Saczuk, Jerzy; Czeczelewski, Jan (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: The analysis of literature revealed close similarities concerning morphological features in groups of people performing the same work, practising the same sport or studying in the same field of study. In the present situation of the demographic low and strong competition on the educational market, the issues of the level of education as well as competences and predispositions of students are discussed more and more often. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim: The aim of the work was to analyse somatic development of male students from various fields of study at the Faculty of Physical Education and Sport in Biala Podlaska. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: The material included anthropometric data of 175 first-year students of the Faculty of Physical Education and Sport in Biala Podlaska. The analysed cohort of men was divided into groups according to the field of study. The measurements of anthropometric features indispensable for calculating BMI, WHR and body composition were made with the use of Martin and Saller technique. In order to describe the collected variables, sample size (n), arithmetic mean ( x ~ ) and standard deviation (SD) were used. Differences between the selected groups concerning the analysed features were estimated with the use of Student’s t-test for independent data. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: The findings were in line with publications of other authors analysing the correlations between body build and the field of study. Therefore, it should be concluded that the selection for physical education studies to a large extent determines body build of the students. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: The observed differences between groups concerning fat-free mass and the level of adiposity as well as its distribution may have stemmed from the differences in lifestyle of the examined men that resulted, inter alia, from their field of study